A higher bid : how to transform special event fundraising with strategic auctions - Kingston, Kathy (Hoboken, New Jersey : Wiley, 2015)
"Transform fundraising events into long-term revenue with expertauction advice A Higher Bid is the nonprofit school and organizationguide to planning and executing more exciting, more lucrativespecial event fundraisers. In this book, award-winning consultant, fundraiser, speaker, and professional auctioneer Kathy Kingstonshares her proprietary and proven approaches to audiencedevelopment, board empowerment, leadership succession, guestcultivation and engagement, and donor development. You'll learn howlive auctions, special appeals, innovative icebreakers, silentauctions, and new technologies can help increase revenue, and howto execute these events in a way that translates to a strongerdonor base for long-term giving. Kingston describes how to matchthe guest list and catalog for better results, and reveals thestrategies professional auctioneers use to curate the right auctionitems and discover the right people to generate optimum revenue andengage donors. This book offers a fresh approach to fundraising, showing youhow charity benefit auctions can be made a centerpiece offundraising special events to drive both short- and long-termfundraising goals while providing a fun and inspiring opportunityto generate awareness and keep supporters excited about themission. Using Kingston's proven framework, you'll learn effectiveways to: Strategically increase high-profit revenue streams Increase your organization's donor base Empower the board toward efficiency and productivity Engage supporters more deeply and keep them invested Donors are the lifeblood of any nonprofit organization, andsustainable revenue depends upon their high engagement andwillingness to give. Well-executed benefit and charity auctionshave proven to be effective fundraisers for nonprofits, associations, and schools of all types, and A Higher Bid isthe expert guide to optimizing these special events for maximumimpact"--
Chapter 5: Attract the Right People FirstObsess on Strategic Audience Development; A Philanthropic Approach to Audience Development; Attract More High Bidders; Draw on Your Development Professionals Expertise; Empower Your Community of Champions; The Super Connectors; Get Rid of Your Ticket Committee; Kathy's Top Strategies for Audience Development; Five Mistakes You'll Want to Avoid; We Sold Out! Create the Expectation to Give; Make Your Event a Signature Networking Opportunity; Conclusion; Chapter 6: Procure Incredible Auction Items; It's All about Relationships.
Machine generated contents note: Introduction Chapter 1. The Shift: Event Transaction to Philanthropic Transformation Chapter 2. Bid High and Prosper: Are Auctions Right For You? Chapter 3. Energize and Empower Your Board and Team Chapter 4. Make Your Auctioneer Your Quarterback Chapter 5. Attract The Right People First Chapter 6. Procure Incredible Auction Items Chapter 7. Make Your Show Flow Chapter 8. Communicate Donor Impact Chapter 9. Leverage New Technology Chapter 10. Optimize Silent Auctions For Loud Results Chapter 11. Maximize the True Worth of Your Live Auction Chapter 12. Ignite Generosity With Fund A Need Special Appeals Chapter 13. Add Strategic Income Streams and Fun Chapter 14. Keep the Money Flowing References.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Benefit auctions; Fund raising; Special events -- Planning; Special events -- Planning; Benefit auctions; Fund raising; Special events -- Planning; Electronic books